The Effect of Cognitive Puzzle Therapy on the Independence Level of Elderly with Dementia in Nursing Home East Jakarta - Wahyudi, Dheni; Anwar, Syamsul; Herlinah, Lily (STIKep PPNI Jawa Barat, 2024)
Aims: This study aims to identify the effect of puzzle cognitive therapy on the level of independence of elderly people with dementia in nursing homes. Method : the research used a quasi-experimental pre-post design with control group design. Sampling was taken using a total sampling technique, 24 respondents in the intervention group and 24 in the control group. Puzzle therapy was carried out for 9 sessions. Measurement of independence used the MMSE (Mini mental status examination) questionnaire and the Katz Index. Analysis with dependent t-test at significance 0.05 (CI 95%) and GLM-RM (General Linear Model Repeated Measure). Results: The results of the paired T test in the intervention group produced a p-value of 0.000, while the control group had a p-value of 0.043. dependent T test and Greenhouse-Geisser (sig) with p value 0.00. Elderly people who are given puzzle activities improve the health and well-being of elderly people with cognitive decline Conclusion: puzzle therapy can improve increasing independence in elderly people with dementia.